2020
DOI: 10.1016/s2589-7500(20)30246-6
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability with photoplethysmography in 8 million individuals: a cross-sectional study

Abstract: Background Heart rate variability, or the variation in the time interval between consecutive heart beats, is a non-invasive dynamic metric of the autonomic nervous system and an independent risk factor for cardiovascular death. Consumer wrist-worn tracking devices using photoplethysmography, such as Fitbit, now provide the unique potential of continuously measuring surrogates of sympathetic and parasympathetic nervous system activity through the analysis of interbeat intervals. We aimed to leverage wrist-worn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 30 publications
3
87
0
Order By: Relevance
“…In contrast, the rise of consumer WDs, which can be used on the wrist, chest, wrist, or finger, provided the opportunity to monitor HRV in a practical, simple, and regular basis and measure the impact of active lifestyles on autonomic health. For instance, one study that collected data from Fitbit consumer wrist-worn devices in more than 8 million users showed that increased daily physical activity across age is associated with improved HRV in a dose-dependent manner [ 61 ]. These results are in line with another large longitudinal study that included 985 older adults and showed that higher total leisure-time physical activity, walking distance, and walking pace are associated with better indices of 24-h Holter HRV [ 62 ].…”
Section: Monitoring Cardiac Function and Cardiovascular Healthmentioning
confidence: 99%
“…In contrast, the rise of consumer WDs, which can be used on the wrist, chest, wrist, or finger, provided the opportunity to monitor HRV in a practical, simple, and regular basis and measure the impact of active lifestyles on autonomic health. For instance, one study that collected data from Fitbit consumer wrist-worn devices in more than 8 million users showed that increased daily physical activity across age is associated with improved HRV in a dose-dependent manner [ 61 ]. These results are in line with another large longitudinal study that included 985 older adults and showed that higher total leisure-time physical activity, walking distance, and walking pace are associated with better indices of 24-h Holter HRV [ 62 ].…”
Section: Monitoring Cardiac Function and Cardiovascular Healthmentioning
confidence: 99%
“…HRV can evaluate symptom severity and progression, stability, and treatment responses [ 60 ]. For example, a recently published study analyzes the HRV for more than eight million people collected with a sensor based on photoplethysmography activity [ 61 ]. It shows how the HRV parameters (in the temporal and frequency domains) change with age, gender, and during the day.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if, and to what extent, psychological and physiological measures of stress are alternative or complementary by nature [34]. Thus, collecting physiological data from wearable devices to monitor stress [35,36] could be used to validate the association with computer mouse movements. Fifth, the sources of stress were not identified, which is important for managing stress.…”
Section: Limitationsmentioning
confidence: 99%